Pituitary metastasis arising from hepatocellular carcinoma: a case report and update of the literature = Hypophysenmetastase bei hepatozellulärem Karzinom : ein Case Report und Aktualisierung der Literatur - Rodriguez, Isaac; Vogel, Lena; Dreher, Constantin; Cherkezov, Asan; Giordano, Frank Anton; Froelich, Matthias F.; Ebert, Matthias; Teufel, Andreas; Boda-Heggemann, Judit (Zeitschrift für Gastroenterologie, 2024)
Hepatocellular carcinoma (HCC) is the sixth most common neoplasia and the third leading cause of cancer-associated deaths worldwide. Most cases arise in patients with cirrhosis, and early detection through periodic screening can make it potentially curable. The presence of extrahepatic metastases (EHM) affects treatment decisions and curability. The lungs are the most common site for EHM, followed by lymph nodes, bones, and the adrenal glands. Interestingly, approximately only 15 cases of HCC metastasizing to the pituitary gland have been reported so far. The most common symptoms of pituitary metastasis (PM) arising from HCC are nerve palsies affecting the third, fourth, and sixth cranial nerves. Other symptoms, such as diabetes insipidus or pituitary insufficiencies, are present in a minority of cases. Detecting PM is difficult given its rarity. Gold-standard treatments for these patients have not yet been established, but the prognosis is dismal, with a median overall survival of only 4.5 months. In this paper, we present an interesting case of PM as the first symptom of an HCC in a 75-year-old female. We also present an overview of all cases reported to date with emphasis on symptom presentation and survival after diagnosis. Given the improvement of systemic therapy, more cases are diagnosed in both oligometastatic and palliative conditions. Therefore, better approaches and treatment modalities for extrahepatic metastases due to HCC should be defined.
Artikel online veröffentlicht: 15. Januar 2024
Gesehen am 10.06.2024